2023
DOI: 10.1007/s00127-023-02508-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Youth Flexible Assertive Community Treatment: outcomes of an 18-month observational study

Abstract: Purpose This Multicenter Youth Flexible ACT Study examined the effect of Youth Flexible Assertive Community Treatment on symptomatic, social, and personal recovery outcomes of adolescents dealing with multifaceted psychiatric and social care needs who do not readily engage in regular office-based mental health services. Methods Newly admitted clients (n = 199) aged 12–24 years from 16 Youth Flexible ACT teams participated in this observational prospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…Their overall ndings were that clients in the ICM groups were most likely to remain with the service, show an improvement in their general functioning, have accommodation, be employed, and tended to spend less time in hospitals. Flexible ACT programs with youth who don't typically engage with regular mental health services have also been shown to improve their mental health symptomology, and social and personal recovery [20].…”
Section: Discussionmentioning
confidence: 99%
“…Their overall ndings were that clients in the ICM groups were most likely to remain with the service, show an improvement in their general functioning, have accommodation, be employed, and tended to spend less time in hospitals. Flexible ACT programs with youth who don't typically engage with regular mental health services have also been shown to improve their mental health symptomology, and social and personal recovery [20].…”
Section: Discussionmentioning
confidence: 99%
“…Our observational cohort study revealed an overall enhancement in clients’ attitudes toward education and work. However, this positive shift did not result in more adolescents accessing appropriate education or employment opportunities during the 18 months of Youth Flexible ACT (Broersen et al, 2023 ). A mental healthcare worker with a broad network and specialized training (such as IPS, preferably enhanced with cognitive remediation; Killackey et al, 2019 ; Erickson, 2021; Van Duin et al, 2021 ) may improve outcomes in this domain.…”
Section: Discussionmentioning
confidence: 99%
“…Teams not previously certified were audited as soon as possible, and other teams were audited as close to the certificate's expiration date as possible (certificates are valid for three years). Mental health workers were asked to complete a ‘content of care questionnaire’ 6 months after the baseline measurement of the cohort study (Broersen et al, 2023 ), with two follow-up measurements (12 and 18 months after baseline), to measure the content of treatment interventions provided in teams.…”
Section: Methodsmentioning
confidence: 99%